ADAMTS13 autoantibodies cloned from patients with acquired thrombotic thrombocytopenic purpura: 2. Pathogenicity in an animal model. Issue 7 (4th April 2016) - Ostertag, Eric M.; Bdeir, Khalil; Kacir, Stephen; Thiboutot, Michelle; Gulendran, Gayathri; Yunk, Lenka; Hayes, Vincent M.; Motto, David G.; Poncz, Mortimer; Zheng, X. Long; Cines, Douglas B.; Siegel, Don L.
Abstract : BACKGROUND: Acquired thrombotic thrombocytopenic purpura (TTP) is a potentially fatal disease in which ultralarge von Willebrand factor (UL‐VWF) multimers accumulate as a result of autoantibody inhibition of the VWF protease, ADAMTS13. Current treatment is not specifically directed at the responsible autoantibodies and in some cases is ineffective or of transient benefit. More rational, reliable, and durable therapies are needed, and a human autoantibody‐mediated animal model would be useful for their development. Previously, TTP patient anti‐ADAMTS13 single‐chain variable‐region fragments (scFv's) were cloned that inhibited ADAMTS13 proteolytic activity in vitro and expressed features in common with inhibitory immunoglobulin G in patient plasma. Here, pathogenicity of these scFv's is explored in vivo by transfecting mice with inhibitory antibody cDNA. STUDY DESIGN AND METHODS: Hydrodynamic tail vein injection of naked DNA encoding human anti‐ADAMTS13 scFv was used to create sustained ADAMTS13 inhibition in mice. Accumulation of UL‐VWF multimers was measured and formation of platelet (PLT) thrombi after focal or systemic vascular injury was examined. RESULTS: Transfected mice expressed physiological plasma levels of human scFv and developed sustained ADAMTS13 inhibition and accumulation of unprocessed UL‐VWF multimers. Induced focal endothelial injury generated PLT thrombi extending well beyond the site of initial injury, and systemic endothelial injury induced thrombocytopenia, schistocyte formation, PLT thrombi, and death. CONCLUSIONS: These results demonstrate for the first time the ability of human recombinant monovalent anti‐ADAMTS13 antibody fragments to recapitulate key pathologic features of untreated acquired TTP in vivo, validating their clinical significance and providing an animal model for testing novel targeted therapeutic approaches.